The complete mitochondrial genome of comma, polygonia c-aureum (Lepidoptera: Nymphalidae: Nymphalinae) - Qing-Hui Shi; Jian-Hong Xing; Xi-Hua Liu; Jia-Sheng Hao (Mitochondrial DNA. Part B. Resources, 2018)
The mitochondrial genome (mitogenome) of Polygonia c-aureum (Lepidoptera: Nymphalidae: Nymphalinae) is determined to be 15,209 bp in length and shows AT bias (80.6%). Similar to other butterflies, it contains 37 typical mitochondrial genes and one AT-rich region (D-loop). All protein-coding genes (PCGs) started with ATN, except for cox1 gene with CGA(R), which is often found in other butterflies, and seven PCGs harbour the typical stop codon TAA, whereas cox1, cox2, nad3, nad5, nad4 and nad1 end with a single T. The rrnL and rrnS genes are 1332 bp and 773 bp in length, respectively. The 342 bp AT-rich region contains non-repetitive sequences, but harbour several features common to the lepidopterans, including the motif ATAGA followed by a 19-bp poly-T stretch and a microsatellite-like (TA)8 element preceded by the ATTTA motif. The complete mitogenome sequence provided here would be useful for further understanding the taxonomy and phylogeny of Nymphalinae.